Transient hyperphosphatasemia: A case report - Sahu, Vinay Kumar (Indian Journal of Child Health, 2016)
Transient hyperphosphatasemia (THP) is characterized by temporary elevation of serum alkaline phosphatase (AP). We report a case of a 26-month-old girl referred for slow growth and found to have THP as AP levels returned to normal without active treatment. THP is a benign condition in healthy children, which resolves spontaneously without any intervention. In the absence of signs and symptoms of any underlying liver, bone or gastrointestinal disease, isolated elevation of AP levels should alert the clinician to a diagnosis of THP to avoid expensive, extensive, and unnecessary investigations.